Lectures on the Psalms - Didymus, approximately 313-approximately 398; Hicks, Jonathan (Jonathan Douglas), 1984- (Downers Grove, IL : IVP Academic, 2024)
"Over the course of his career, early Christian theologian Didymus the Blind wrote numerous theological treatises and exegetical works. This ACT volume presents Didymus's lectures on portions of the Psalms as they were originally presented to his students, allowing us to learn at Didymus's feet and find comfort in the Word of God"--
Translation of a Greek manuscript known as Eis Psalmous discovered in 1941 near the ruins of an ancient monastery dedicated to Saint Arsenius the Great.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries -- Early works to 1800.; Bible. -- Criticism and interpretation -- Early works to 1800.